2020
DOI: 10.1186/s12866-020-02024-x
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing analysis of the rhizosphere arbuscular mycorrhizal fungi (AMF) community composition associated with Ferula sinkiangensis

Abstract: Background Ferula sinkiangensis is an increasingly endangered medicinal plant. Arbuscular mycorrhiza fungi (AMF) are symbiotic microorganisms that live in the soil wherein they enhance nutrient uptake, stress resistance, and pathogen defense in host plants. While such AMF have the potential to contribute to the cultivation of Ferula sinkiangensis, the composition of AMF communities associated with Ferula sinkiangensis and the relationship between these fungi and other pertinent abiotic factors still remains to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The slope position is an important topographic factor, and there is a significant difference in species diversity with the change in slope position [21]. Our results found that the alpha diversity of the downslope rhizosphere and bulk soil samples is higher than that of the upslope samples (Figure 2).…”
Section: Community Composition Of C Camphora Root-associated Bacterial Microbiomementioning
confidence: 66%
See 1 more Smart Citation
“…The slope position is an important topographic factor, and there is a significant difference in species diversity with the change in slope position [21]. Our results found that the alpha diversity of the downslope rhizosphere and bulk soil samples is higher than that of the upslope samples (Figure 2).…”
Section: Community Composition Of C Camphora Root-associated Bacterial Microbiomementioning
confidence: 66%
“…It is reported that the slope position is an important topographic factor that controls the microenvironment heterogeneity by affecting plant temperature, light, physical and chemical properties of the soil, and water level [19,20]. Although slope position is not a direct ecological factor determining the survival of microorganisms, it can affect the distribution of microorganisms by controlling the spatial-temporal distribution of a series of ecological factors and their combinations [21]. Therefore, the soil type and slope position of plants are closely related to the microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…The Glomus was the most abundant genus reported in forest ecosystems (Chen et al, 2007;Lu et al, 2019;Jing et al, 2020;Ji et al, 2021), reclamation land (Ezeokoli et al, 2020), desert vegetative sites (Vasar et al, 2021), agroecosystems (Wang et al, 2020) and saline ecosystems (Sheng et al, 2019) indicating its wide adaptation to diverse ecosystems. Additionally, studies found that the AMV4.5NF/AMDGR primers favored the amplification of Glomeraceae sequences (Luo et al, 2020), which may also have resulted in the dominance of Glomeraceae and Glomus at the family and genus levels, respectively. Contrary to our results, Sheng et al (2017) reported that Rhizophagus dominated in roots and soils along a chronosequence of blank locust plantations.…”
Section: Changes In Arbuscular Mycorrhizal Fungal Community Diversity and Community Structurementioning
confidence: 99%
“…Especially in soil, K was the first factor that contributed to 21.7% of the total variation (Figure 8). Several studies have reported that K availability is an important driver of AM fungal community composition due to the accumulation of K content with stand age grew (Qin et al, 2017;Sheng et al, 2017;Luo et al, 2020). High N input can result in the decline of AM fungal abundance, and low N availability conditions can effectively improve the ability of AM fungi to transport N elements to host plants (Xiao et al, 2019).…”
Section: Factors Driving Arbuscular Mycorrhizal Fungal Communitiesmentioning
confidence: 99%
“…Also, the host plants can have a controlling effect on AMF colonization ( 30 ). So far, most studies have only focused on the sampling sites at different locations to examine the correlation between soil physicochemical factors and AMF communities ( 31 33 ). Apart from soil physicochemical properties, soil enzyme activity, soil temperature, soil moisture, and the relative contributions of relevant environmental factors such as altitude, relative air humidity, soil pH, and available phosphorus (P), kalium (K), and magnesium (Mg) can influence the AMF spore production and root colonization ( 32 , 34 36 ).…”
Section: Introductionmentioning
confidence: 99%